La ricerca della Sapientia in De resurr. 278-292 (CPL 1463) - De Gaetano, Miryam (Augustinianum, 2018)
The aim of this study is to analyse a passage of the pseudoepigraphic Carmen de resurrectione (vv. 278-292) which relates to insipientes, interpreted as those who do not accept that the rational observation of nature proves the existence of a unique creator God. Such a refusal is believed to make them worthy of eternal damnation. The resulting concept of sapientia involves both ratio and voluntas; it is also connected with gnoseology and soteriology. A similar concept can be found in the Aquitanian poetry of the fifth century and in the theology of the so-called Semipelagians. This similarity calls into question the traditional dating and the supposed area of origin of the Carmen.